Evaluation of Red Pitaya (Hylocereus polyrhizus) Peel as A Feed Additive in Sangkuriang Catfish (Clarias gariepinus) - Putri, Febiyanti Ivana; Sukarti, Komsanah; Agustina (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This study aimed to evaluate the effect of adding red pitaya peel flour with different doses in feed on hematological parameters, growth performance, and utilization of sangkuriang catfish feed. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Sangkuriang catfish seeds with an average size of 27.79 ± 3.31 g were reared as many as 10 fish for 25 days with a water volume of 30 L. The fish were given treatment feed with doses of (P0) 0%, (P1) 5%, (P2) 10%, and (P3) 20% red pitaya peel flour in the feed. Feeding was carried out three times a day ad satiation. The results showed that the hematological parameters of Sangkuriang catfish were still in the normal range with the addition of red pitaya peel flour up to a dose of 20% in the feed. The addition of red pitaya peel flour had a significant effect on the absolute weight growth and feed conversion ratio of Sangkuriang catfish but had no significant effect on the specific growth rate (P>0.05). The treatment dose of 5% red pitaya in feed (P1) gave the highest absolute weight growth of 28.65 g, and the lowest feed conversion ratio was 1.30. Based on the results of this study, a dose of 5% red pitaya peel flour in feed has the potential as a feed additive in catfish cultivation.